Instructor attribute and feedback to empower mature learners in ODL education - Abdullah, Zaleha (International Association of Online Engineering, 2021)
With the outbreak of Covid-19, Open and Distance Learning (ODL) has become even popular particularly among those who aim to pursue postgraduate studies. ODL provides alternative for many to study while working or while raising a family. Nevertheless, the lack of student engagement and noncompletion rate in ODL programs were reported higher than in traditional programs. One of the main factors is due to the instructor-student interaction issue. The objective of this qualitative study was to understand the issue by looking at instructor attributes and types of feedback required by the students. The data were collected via semi-structured interviews with a small sample of university postgraduate students and academics in Malaysia and were analysed using thematic analysis and data triangulation. The results show two factors that need attention to improve instructor-student interaction and make ODL a better learning option for mature learners: instructor empathy and feedback to empower learners. These findings cannot be generalised without further research but are able to provide some information on the important factors to consider in preparing instructors for learning delivery completely online.